The Influence of Public Awareness of Rights and Obligations in Creating a Harmonious and Just National Life - Nur Aziz Rio Andika; Ardian Al Fajri; Suparmi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Citizens' rights and obligations play a vital role in creating a harmonious and just national life. However, an imbalance in the understanding and implementation of both can lead to various social problems, necessitating collective awareness and commitment from the state and society to realize a just national life. Therefore, this study aims to analyze the influence of public awareness on the implementation of citizens' rights and obligations in realizing a harmonious and just national life. Furthermore, this study also aims to examine the role of civic education, Pancasila and religious values, and political participation in shaping national awareness, as well as to identify weaknesses and gaps in previous research to provide direction for more comprehensive follow-up research. A literature search using articles with keywords related to public awareness and citizen obligations, focused on journals published less than 50 years ago, yielded more than 50 articles. After a selection process based on criteria, 20 journals were selected for in-depth analysis, covering important data such as researchers, methods, subjects, and main findings. The research found that public awareness as citizens, influenced by education, morality, law enforcement, political participation, and civic education, plays a crucial role in creating a harmonious and just national life. Research shows that low levels of legal and political awareness can lead to violations, apathy, and social conflict.